Implementasi Pengelolaan Kurikulum dalam Peningkatan Kualitas Pendidikan Berdasarkan Instrumen Akreditasi Satuan Pendidikan (IASP) Tahun 2020 di MIN 2 Kota Bandung - Hodijah, Anisa Siti; Nugraha, Mulyawan Safwandy (Lembaga Yasin AlSys, 2024)
The curriculum is crucial in enhancing education quality. One way to demonstrate the quality of an educational institution is through accreditation. Accreditation is the process of comparing field facts with eight standards. This research aims to understand how curriculum management implementation improves education quality based on the 2020 Education Unit Accreditation Instrument (IASP). This study uses a qualitative method with a case study approach. Data collection was conducted through interviews and document reviews according to IASP 2020. The results show that curriculum planning has been well executed, including regular meetings every semester with subject teachers and the curriculum team to discuss and determine school policies. Curriculum implementation is evidenced by providing support to teachers who experience difficulties in applying the existing curriculum. Curriculum evaluation has been well conducted in terms of input, process, and output aspects.